UPAYA MENINGKATKAN HASIL BELAJAR IPA MENGGUNAKAN MODEL PENGAJARAN LANGSUNG SISWA KELAS V B SD NEGERI 004 BAGAN BESAR - ', Misnah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This classroom action research aims to improve learning outcomes fifth grade sciencestudents and SD Negeri 004 Bagan Besar Dumai through direct teaching model. The subjectswere students of class V B SD Negeri 004 Bagan Besar Dumai totaling 27 students consistingof 16 male students and 11 female students. The parameters measured in the study is theresult of student learning, student activities, complete learn student and teacher activities. Theresults showed an average absorption of students based daily test cycle I obtained average(82.03) both categories and is based on the second cycle of daily test gained an average(93.86) is very good category. Mastery learning students in the first cycle individually(85.19%) completed. While on the second cycle (88.89%) completed. Activities of students inthe first cycle obtained an average (72.62%) enough, the second cycle was obtained average(77.41%) categories. For teachers in the first cycle of activity gained an average (90%) bothcategories while in the second cycle obtained an average (100%) very good category. It canbe concluded from the results of fifth grade students learn science and SD Negeri 004 BaganBesar Dumai can be improved through the application of direct teaching model.